Evaluation Of Resting Energy Expenditure For Solid Tumor And Leukemia Patients In Penang General Hospital, Malaysia - Khor, Su Mee (2012)
Malnutrition is common in cancer patients. Generally, it is believed that Resting Energy Expenditures (REE) is elevated in cancer patients and is contributed to the development of malnutrition. Thus, accurately assessing Resting Energy Expenditure is important in planning adequate nutrition support. Current studies showed Harris Benedict, Schofield and WHO equations were overestimating the Resting Energy Expenditure in Asian. However, these equations were still commonly use in clinical practice in Malaysia. Meanwhile, the Ismail equation which derived from Malaysian healthy subjects was still not widely used in Malaysia. Thus, the purpose of this study was to measure and compare the REE for solid tumor, leukemia and control group and determined which predictive equation is more accurate to estimate the REE in Malaysian cancer and healthy group. Resting Energy Expenditure was measured in 60 cancer patients and 60 healthy subjects, age ranged from 18 to 60 years old and with Body Mass Index of 18.5 to 25.0 kg/m2 by using Indirect Calorimetry. The measured REE were compared among cancer and healthy group and also compared to 9 predicted REE respectively (Harris Benedict, Schofield, WHO, Mifflin-St Jeor, Oxford, Jia, Liu, Ismail equation and Quick method). Statistical analysis was carried out by using SPSS with the method of independent t-test, paired t test and one way ANOVA